2018
DOI: 10.1139/gen-2017-0208
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal transfers of LTR retrotransposons in seven species of Rosales

Abstract: Horizontal transposable element transfer (HTT) events have occurred among a large number of species and play important roles in the composition and evolution of eukaryotic genomes. HTTs are also regarded as effective forces in promoting genomic variation and biological innovation. In the present study, HTT events were identified and analyzed in seven sequenced species of Rosales using bioinformatics methods by comparing sequence conservation and K/K value of reverse transcriptase (RT) with 20 conserved genes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…. However, the number of intergenomic syntenic LTR retrotransposons can also be affected by environment, genetic background, and horizontal transfer (El Baidouri et al, 2014; Hou et al, 2018). In conclusion, combining the results of πN / πS value, phylogenetic tree, and syntenic analyses, many LTR retrotransposons among grapevine relatives were formed after species divergence through the duplication of limited common ancestral LTR retrotransposons (Figs. )…”
Section: Discussionmentioning
confidence: 99%
“…. However, the number of intergenomic syntenic LTR retrotransposons can also be affected by environment, genetic background, and horizontal transfer (El Baidouri et al, 2014; Hou et al, 2018). In conclusion, combining the results of πN / πS value, phylogenetic tree, and syntenic analyses, many LTR retrotransposons among grapevine relatives were formed after species divergence through the duplication of limited common ancestral LTR retrotransposons (Figs. )…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the timing of a single ERV integration event can be estimated by measuring the genetic distance between LTR sequences. The genetic distance between 5'-and 3'-LTRs of an ERV increases with its integration time [37,38]. To explore the temporal dynamics of the LTW ERV lineages, we retrieved all the complete LTW ERVs and calculated the genetic distance between their 5'-and 3'-LTRs (Fig 5A).…”
Section: Temporal Dynamics Of Cetacean Erv Amplificationmentioning
confidence: 99%
“…El Baidouri et al [119] demonstrated HTTs between at least 26 plant species. Hou et al [120] found HTT events among seven Rosales species. Dias et al [116] hypothesized the HTT of an LTR retrotransposon called “Copia25” between the ancestors of the genera Ixora and Musa .…”
Section: Structure Diversity Dynamics and Function Of Retrotranmentioning
confidence: 99%
“…Dias et al [116] hypothesized the HTT of an LTR retrotransposon called “Copia25” between the ancestors of the genera Ixora and Musa . Although the mechanisms of HTT remain unclear in plants, HTT represents an important way for host genomes to innovate and evolve [120].…”
Section: Structure Diversity Dynamics and Function Of Retrotranmentioning
confidence: 99%